Media power and right-wing terrorism: when saving Peru is the only thing left (Revista revoluciones, 2021)
The manuscript takes stock of a number of problems that occur in Peru, motivated by media power and the complex right-wing terrorism. Both mechanisms of manipulation, they make a similar inflection to destroy the candidate of humble profession, but of enormous significance for Peruvians with dignity. As a result, the current leftist spokesperson has been supported by the disfigured majority at every moment in Republican history, that majority motivated to make substantive change in the country, finally breaking the dominant patterns implanted since colonization.
Keywords: Media power; politics; manipulation; political right; revolution